Titik Sentral (視点) Dalam Bahasa Jepang - Ariani Tanjung (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
In Japanese language, shiten is an event drawn in the sentence structures, if it becomes the central point of a naturally-accepted event. Shiten is also the person who becomes the speaker’s object (syudai). The research discusses about shiten focused on service take and give verbs (jujuhyogen) in Ukemi （受身） shieki（使役）（受身）,（使役）and jujuhyougen（授受の表（授受の（使役（授受現） . It applies a qualitative method and it means that the research explains the data observed as it is.